Bandwidth enhancement of compact microstrip rectangular antennas for UWB applications - S. Elajoumi; A. Tajmouati; J. Zbitou; A. Errkik; A. M. Sanchez; M. Latrach (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
In this paper design of microstrip patch antennas are presented for ultra wideband (UWB) applications. The designed antennas have good matching input impedance in a wide frequency band covering the UWB frequency band which is defined by the FCC. The proposed antennas consist of rectangular patch which is fed by 50Ω microstrip line. These antennas are investigated and optimized by using CST microwave studio, they are validated by using another electromagnetic solver HFSS. The proposed antennas are designed and optimized taking into account the optimized of the ground by using Defected Ground Structure (DGS) in order to improve the frequency band of microstrip antenna. Hence, the impedance and surface current of the antenna structures are affected by DGS. As will be seen, the operation bandwidth of the proposed antennas is from 3 to 15 GHz (return loss≤-10 dB), corresponding to wide input impedance bandwidth (133.33%), with stable omnidirectional radiation patterns and important gain. A good agreement has been obtained between simulation and measurement results in term of bandwidth clearly show the validity of the proposed structures. These antennas are useful for UWB applications, may be able to potentially minimize frequency interference from many wireless technologies i.e WLAN, WiMAX. Details of the antennas have been investigated numerically and experimentally.